A preparation method for a photocatalytic water decomposition hydrogen production catalyst based on CdS nanoflower balls composite ZnIn2S4 nanosheets
Synthesis of heterojunction photocatalysts of CdS nanoflower sphere composite ZnIn2S4 nanosheets by hydrothermal method, solving the problem of insufficient performance of ZnIn2S4 and CdS photocatalysts in photocatalytic decomposition of water and hydrogen production, and achieving efficient photocatalytic decomposition of aquatic hydrogen , and the materials are simple to prepare and low cost, suitable for large-scale promotion.
Patent Information
- Application Number
- CN202310669279.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-07
AI Technical Summary
The existing ZnIn2S4 and CdS photocatalysts have problems such as easy recombination of photogenerated carriers, poor stability, and serious photocorrosion when photocatalyzed and produced hydrogen, resulting in unsatisfactory photocatalytic performance.
The heterojunction photocatalyst of CdS nanoflower spheres composited with ZnIn2S4 nanosheets was synthesized by hydrothermal method to form a stable heterojunction to improve photocatalytic performance.
It realizes efficient decomposition of aquatic hydrogen under visible light excitation, has a regular material morphology, is simple in preparation, is low in cost, and is suitable for large-area applications.
Smart Images

Figure CN116726950B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen energy technology, and in particular to a method for preparing a catalyst for photocatalytic water decomposition and hydrogen production based on CdS nano-flower balls composited with ZnIn2S4 nano-sheets. Background Art
[0002] At present, the extensive use of fossil energy not only leads to serious environmental pollution in human society, but also poses a serious threat to human survival and life. With the increasing severity of energy and environmental problems, there is an urgent need to seek clean and pollution-free energy to replace traditional non-renewable energy. Hydrogen energy is a clean and pollution-free fuel with high combustion calorific value and only produces water. It is considered to be an ideal clean and renewable energy source, so it has attracted the attention of more and more scholars in recent years. Unlimited solar energy can be converted into valuable chemical energy through photocatalytic hydrogen production without generating secondary pollution. Overcoming the problem of low efficiency of photocatalytic hydrogen production is still a great challenge. The properties of semiconductors directly determine the photocatalytic performance. Semiconductor materials have unfavorable conditions such as limited visible light absorption range, difficult separation of photogenerated electrons and holes, and poor stability. Therefore, in order to solve the above problems, it is necessary to reasonably design excellent photocatalysts to improve the photocatalytic performance.
[0003] In recent years, transition metal sulfide indium zinc sulfide (ZnIn2S4) has attracted more and more attention from scholars because of its adjustable band gap of 2.06 ~ 2.85 eV, high physical and chemical stability, low toxicity compared with traditional metal sulfides, wide range of raw materials and relatively easy preparation process. However, the photocatalytic performance of pure ZnIn2S4 is not satisfactory, mainly because its photogenerated carriers are easy to recombine. In view of this, it is necessary to design a reasonable and efficient ZnIn2S4-based photocatalyst to improve its photocatalytic performance. Pure CdS has attracted much attention because of its suitable band gap (2.40 eV) and high visible light absorption efficiency. However, due to its susceptibility to photocorrosion, the difficulty in separating photogenerated electrons and holes, and the poor reuse rate of severe photocorrosion, its photocatalytic water decomposition hydrogen evolution yield is not ideal. Studies have found that ZnIn2S4 can effectively improve its photocatalytic performance and hydrogen production efficiency by coupling with a semiconductor with a matching band gap to form a stable and effective heterojunction.
[0004] Based on the above technical background, in order to solve the problems existing in the above-mentioned pure ZnIn2S4 and CdS, the present technical invention combines the two by a simple hydrothermal method to synthesize CdS nanoflower balls composite ZnIn2S4 nanosheets (CdS / ZnIn2S4) heterojunction photocatalyst to obtain efficient photocatalytic decomposition of water and hydrogen evolution performance. Related technologies have not been reported. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems existing in the prior art and to provide a method for preparing a catalyst for photocatalytic water decomposition and hydrogen production based on CdS nano-flower balls composited with ZnIn2S4 nano-sheets.
[0006] To achieve the above object, the technical solution provided by the present invention is: a method for preparing a catalyst for photocatalytic decomposition of water to produce hydrogen based on CdS nano-flower balls composited with ZnIn2S4 nano-sheets, comprising:
[0007] (1) Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2 . 2H2O and 3 mmol InCl3 . 4H2O was added to 250 mL of deionized water and stirred for 30 min to obtain a mixed solution A, and then an excess of thioacetamide was added to the mixed solution A, and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm / min, and washed with deionized water twice to obtain a crude sample, which was dispersed in 200 mL of deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder.
[0008] (2) Synthesis of CdS nanoflowers: 2 mmol Cd(OAc)2 . 2H2O and 6 mmol thiourea were added to 60 mL ethylenediamine in sequence and mixed by ultrasound to obtain a mixed solution B; then the mixed solution B was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS sample powder;
[0009] (3) Synthesis of CdS nano-flower ball composite ZnIn2S4 nanosheet composite material: Take a certain amount of ZnIn2S4 sample powder obtained in step (1), disperse it in 60 mL of ethylenediamine with 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea, and then transfer it to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and react at 100 °C for 8 h. After the reaction is completed, the reaction solution is centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nano-flower ball composite ZnIn2S4 nanosheet.
[0010] Preferably, the amount of ZnIn2S4 added in step (3) is in the range of 100-300 mg.
[0011] Beneficial effects of the present invention:
[0012] 1. The CdS / ZnIn2S4 nanocomposite material prepared in the present invention can effectively decompose water to produce hydrogen under visible light excitation.
[0013] 2. The CdS / ZnIn2S4 nanocomposite material prepared by the present invention has regular morphology, is simple to prepare, has low cost, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0015] Figure 1 This is a scanning electron microscope image of a CdS / ZnIn2S4 nanocomposite material of CdS nanoflower balls and ZnIn2S4 nanosheets prepared in specific example 2 of the present invention;
[0016] Figure 2 The performance diagram of the CdS / ZnIn2S4 nanocomposite material of the CdS nanoflower ball composite ZnIn2S4 nanosheet prepared in the specific embodiment 2 of the present invention for photocatalytic decomposition of water and hydrogen production under visible light excitation DETAILED DESCRIPTION
[0017] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.
[0018] A preferred embodiment of the present invention is a method for preparing a catalyst for photocatalytic decomposition of water to produce hydrogen based on CdS nano-flower balls composited with ZnIn2S4 nano-sheets, comprising:
[0019] (1) Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2 . 2H2O and 3 mmol InCl3 . 4H2O was added to 250 mL of deionized water and stirred for 30 min to obtain a mixed solution A, and then an excess of thioacetamide was added to the mixed solution A, and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm / min, and washed with deionized water twice to obtain a crude sample, which was dispersed in 200 mL of deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder.
[0020] (2) Synthesis of CdS nanoflowers: 2 mmol Cd(OAc)2 . 2H2O and 6 mmol thiourea were added to 60 mL ethylenediamine in sequence and mixed by ultrasound to obtain a mixed solution B; then the mixed solution B was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the solution after the reaction was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS sample powder;
[0021] (3) Synthesis of CdS nano-flower ball composite ZnIn2S4 nanosheet composite material: Take a certain amount of ZnIn2S4 sample powder obtained in step (1), disperse it in 60 mL of ethylenediamine with 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea, and then transfer it to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and react at 100 °C for 8 h. After the reaction is completed, the reaction solution is centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nano-flower ball composite ZnIn2S4 nanosheet.
[0022] In this embodiment, the amount of ZnIn2S4 added in step (3) ranges from 100 to 300 mg. Specific embodiment 1
[0023] Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2 . 2H2O and 3 mmol InCl3 . 4H2O was added to 250 mL of deionized water and stirred for 30 min to obtain a mixed solution A. An excess of thioacetamide (TAA) was added to the mixed solution A and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm / min, washed with deionized water twice, dispersed in 200 mL of deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder.
[0024] Synthesis of CdS nanoflower balls: 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea were added to 60 mL ethylenediamine in sequence and mixed by ultrasound to obtain a mixed solution B. The mixed solution B was then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS sample powder.
[0025] Synthesis of CdS nano-flower ball composite ZnIn2S4 nanosheet (CdS / ZnIn2S4) composite material: 100 mg of ZnIn2S4 was dispersed with 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea in 60 mL of ethylenediamine, and then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 100 °C for 8 h; after the reaction was completed, the reaction solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nano-flower ball composite ZnIn2S4 nanosheet. Specific embodiment 2
[0026] Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2 . 2H2O and 3 mmol InCl3 . 4H2O was added to 250 mL of deionized water and stirred for 30 min to obtain a mixed solution A. An excess of thioacetamide (TAA) was added to the mixed solution A and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm / min, washed with deionized water twice, dispersed in 200 mL of deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder.
[0027] Synthesis of CdS nanoflower balls: 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea were added to 60 mL ethylenediamine in sequence and mixed by ultrasound to obtain a mixed solution B. The mixed solution B was then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS sample powder.
[0028] Synthesis of CdS nano-flower ball composite ZnIn2S4 nanosheet (CdS / ZnIn2S4) composite material: 144 mg of ZnIn2S4 was dispersed with 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea in 60 mL of ethylenediamine, and then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h; after the reaction was completed, the reaction solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nano-flower ball composite ZnIn2S4 nanosheet.
[0029] Reference Figure 1It can be seen that the morphology of the CdS / ZnIn2S4 nanocomposite material synthesized in specific embodiment 2 is uniform and regular; (a) is a scanning electron microscope image of CdS nanoflower balls; (b) is a scanning electron microscope image of ZnIn2S4 nanosheets; (c) is a scanning electron microscope image of CdS / ZnIn2S4 nanocomposite.
[0030] Reference Figure 2 , it can be seen that the photocatalytic decomposition of water and hydrogen production performance of the CdS / ZnIn2S4 nanocomposite material synthesized in specific embodiment 2 under visible light excitation is shown. Specific embodiment 3
[0031] Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2 . 2H2O and 3 mmol InCl3 . 4H2O was added to 250 mL of deionized water and stirred for 30 min to obtain a mixed solution A. An excess of thioacetamide (TAA) was added to the mixed solution A and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm / min, washed with deionized water twice, dispersed in 200 mL of deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder.
[0032] Synthesis of CdS nanoflower balls: 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea were added to 60 mL ethylenediamine in sequence and mixed by ultrasound to obtain a mixed solution B. The mixed solution B was then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS sample powder.
[0033] Synthesis of CdS nano-flower ball composite ZnIn2S4 nanosheet (CdS / ZnIn2S4) composite material: 288 mg of ZnIn2S4 was dispersed with 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea in 60 mL of ethylenediamine, and then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h; after the reaction was completed, the reaction solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nano-flower ball composite ZnIn2S4 nanosheet. Specific embodiment 4
[0034] Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2 . 2H2O and 3 mmol InCl3 . 4H2O was added to 250 mL of deionized water and stirred for 30 min to obtain a mixed solution A. An excess of thioacetamide (TAA) was added to the mixed solution A and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm / min, washed with deionized water twice, dispersed in 200 mL of deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder.
[0035] Synthesis of CdS nanoflower balls: 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea were added to 60 mL ethylenediamine in sequence and mixed by ultrasound to obtain a mixed solution B. The mixed solution B was then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS sample powder.
[0036] Synthesis of CdS nano-flower ball composite ZnIn2S4 nanosheet (CdS / ZnIn2S4) composite material: 300 mg of ZnIn2S4 was dispersed with 2 mmol Cd(OAc)2.2H2O and 6 mmol thiourea in 60 mL of ethylenediamine, and then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h; after the reaction was completed, the reaction solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nano-flower ball composite ZnIn2S4 nanosheet.
[0037] The CdS / ZnIn2S4 nanocomposite material of the CdS nanoflower ball composite ZnIn2S4 nanosheet prepared by the present invention can effectively decompose water to produce hydrogen under visible light excitation. The CdS / ZnIn2S4 nanocomposite material of the CdS nanoflower ball composite ZnIn2S4 nanosheet prepared by the present invention has a regular morphology, is simple to prepare, has low cost, and is suitable for large-scale promotion and application.
[0038] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.
[0039] The above description is only a preferred implementation mode of the present invention. Any technical solution that achieves the purpose of the present invention by substantially the same means belongs to the protection scope of the present invention.
Claims
1. A method for preparing a photocatalytic water decomposition hydrogen production catalyst based on CdS nano-flower balls composite ZnIn2S4 nano-sheets, characterized in that: The preparation method comprises using CdS nano flower balls and ZnIn2S4 nano sheets as components, and synthesizing a CdS / ZnIn2S4 nanocomposite material of CdS nano flower balls and ZnIn2S4 nano sheets by a simple hydrothermal synthesis method, and specifically comprises the following steps: (1) Synthesis of ZnIn2S4 nanosheets: 1.5 mmol Zn(CH3COO)2·2H2O and 3 mmol InCl3·4H2O were added to 250 mL deionized water and stirred for 30 min to obtain a mixed solution A. An excess of thioacetamide was added to the mixed solution A and the stirring was continued for 30 min. After stirring, the solution was placed in a water bath at 95 °C for 5 h, and then centrifuged at 8500 rpm and washed twice with deionized water to obtain a crude sample. The crude sample was dispersed in 200 mL deionized water and ultrasonicated for 30 min. After dispersion, the solution was centrifuged and then dried at 60 °C for 24 h to obtain a ZnIn2S4 sample powder. (2) Synthesis of CdS / ZnIn2S4 nanocomposite materials: A certain amount of ZnIn2S4 sample powder obtained in step (1) was dispersed in 60 mL of ethylenediamine with 2 mmol Cd(OAc)2·2H2O and 6 mmol thiourea, and then transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and reacted at 100 °C for 8 h. After the reaction was completed, the reaction solution was centrifuged and washed, and then dried at 60 °C for 10 h to obtain a CdS / ZnIn2S4 nanocomposite material of CdS nanoflower balls and ZnIn2S4 nanosheets.
2. The method for preparing a photocatalytic water decomposition hydrogen production catalyst based on CdS nano-flower balls composite ZnIn2S4 nano-sheets according to claim 1, characterized in that: The amount of ZnIn2S4 added in step (2) ranges from 100 to 300 mg.
Citation Information
Cited By
ZnIn2S4-coated Bi0. 5Na0. 5TiO3 composite heterojunction photocatalyst as well as preparation method and application thereof
CN121911444A
